A case for a rookie hangman - Fišer, Luboš 1935-1999 (Second Run, 2019)
Made during the '68 crisis, this allegorical satire updates Swift (Gulliver's travels to Laputa and Balnibarbi) and Lewis Carroll, presenting an episodic account of the 35-year-old hero's nightmare journey to a world which he encounters on the other side of a road tunnel. No surprise to discover that it's very much like contemporary Czechoslovakia. Here is absurdity, transgression, jet-black comedy and the unexplained. Shot using graphic inserts, split images, slo-mo and fish-eye lenses, it recreates the mood of Kafka-esque paranoia that writer/director Jurácek had used more directly in his earlier "Joseph Kilián". If its abundant allusions and cross-references are difficult to decipher for the uninitiated, the Czech censors had no such problems - they promptly banned it for 20 years. [www.timeout.com]
Original: Tschechoslowakei 1970
Special features: presented from an HD transfer of the new 4K restoration by the Czech National Film Archive ; Josef Kilián (1963) - Pavel Juráček and Jan Schmidt's acclaimed short feature presented from an HD transfer of its new 4K restoration ; two short films by Juráček and Schmidt: Cars without a home (1959, 7 minutes), Black and white Sylva (1961, 29 minutes) ; the 2017 Projection Booth podcast co-hosted by Mike White, Kat Ellinger, Kevin Heffernan and Peter Hames ; 24-page booklet featuring a new essay on the film by writer and film historian Michael Brooke
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc